Analisis Medication Error di Instalasi Farmasi Rawat Jalan RSPAD Gatot Soebroto Jakarta Pusat - Ayyoehan Tiara Annisa; Susi Ari Kristina; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Medication errors (MEs) have an impact on drug service inaccuracies and endanger patients at risk through a variable number of accidents, so it is necessary to conduct different methods and definitions study. This study aimed to analyze MEs and causing factors in the Outpatient Pharmacy Installation of Gatot Soebroto Army Hospital. A mixed method study between quantitative and qualitative was conducted. A quantitative study was carried out by analyzing outpatient prescriptions to identify MEs with a checklist instrument and interviewing informants to find out some factors causing MEs. After the data generated from an interview, data were collected as a total of causing MEs, so the factors causing MEs could be determined. Data analysis was carried out descriptively. The results showed MEs in each Outpatient Pharmacy Installation of Gatot Soebroto Army Hospital. Errors at the BPJS Outpatient Pharmacy Installation consisted of prescribing errors (41,6%), transcribing errors (4,6%), and dispensing errors 15,7%). Errors at the Kartika Pavilion Outpatient Pharmacy Installation consisted of prescribing errors (12,4%), transcribing errors (2,4%), and dispensing errors (0,7%). BPJS Outpatient Pharmacy Installation has the highest medication errors (61,8%) in Gatot Soebroto Army Hospital compared to the Kartika Pavilion Outpatient Pharmacy Installation (15,5%) which was caused by the number of patients being larger and not comparable with the minimum number of staff. Other factors that cause ME include human factors such as the performance of staff and fatigue, system factors such as manual recipes and the absence of an e-prescription system, and environmental factors such as a busy work environment.